MORTALITAS DAN PERTUMBUHAN CRYPTOLESTES FERRUGINEUS STEPHENS (COLEOPTERA: CUCUJIDAE) PADA BEBERAPA TINGKATAN SUHU RUANG - Pratiwi, NI Putu Eka; Raka, I Dewa Nyoman; Ananda, Komang Dean (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2019)
The research on the mortality and growth of Cryptolestes ferrugineus on IR-64 rice variety at the room temperatures of 20°C, 25°C, 30°C, 35°C and 40°C was done at the Pest Laboratory, Department of Plant Pest and Disease, Agriculture Faculty, University of Brawijaya, Malang. The results showed that C. ferrugineus could not survive at 40°C room temperature. The highest mortality of C. ferrugineus imago occurred at 40°C. Eggs produced by adult C. ferrugineus at 40°C cannot hatch into larvae, so development stops during the egg phase. The number of eggs of C. ferrugineus is produced more at room temperature 25°C than room temperature 20°C, 30°C, 35°C, and 40°C by showing the number of eggs at room temperature 25°C(85.20 items) more higher than the room temperature of 20°C(46.40 items), 30°C(55.40 items), 35°C (63.40 items) and 40°C (10.20 items)